Diminished physiological flexibility is associated with intolerance of uncertainty during affective decision making in adolescence. Issue 4 (December 2014) - Wild, A.; Freeston, M. H.; Heary, S.; Rodgers, J.
Adults with Generalized Anxiety Disorder (GAD) are reported to display discrepancy between self-reported somatic anxiety symptoms and physiological indices. Whilst physiological indices indicate a reduced physiological response, self-report measures reflect the perception of heightened and aversive somatic symptoms. It is unclear whether the discrepancy between perceived and observed somatic arousal in adults with GAD, extends into adolescence. This study aimed to investigate whether in healthy adolescents the degree of intolerance of uncertainty (a core construct in the development of GAD), affected the perception of somatic arousal in anxiety provoking situations, to determine if the discrepancy between perceived and observed physiological arousal, evident in adults with GAD, is present in adolescence. The sample were 33 healthy adolescents recruited from school settings (mean age 12 years) divided in to two groups based on the presence of either high or low intolerance of uncertainty as measured by a brief self-report tool. Differences in physiological arousal, measured via electrodermal activity, were assessed in the two groups during a decision making task used to induce a mild state of anxiety. During the decision making task, adolescents with low intolerance of uncertainty reported lower levels of anxiety relative to a more flexible physiological response pattern, than those with high intolerance of uncertainty. The adolescents with high intolerance of uncertainty reported higher levels of anxiety relative to a less flexible physiological response pattern than those in the low IU group. The results indicate that the pattern of dissociation between physiological and self-reports of somatic symptoms in adults with GAD, is detectable in a sample of healthy adolescents with high intolerance of uncertainty. The study extends the current understanding of anxiety in adolescence and specifies future research, with the potential to improve treatment options for this distressing disorder.